The Metabolic Basis of ILC Plasticity - Pelletier, Abigaelle; Stockmann, Christian (Frontiers in Immunology, 2022)
Innate Lymphoid Cells (ILCs) are the innate counterpart of adaptive lymphoid T cells. They are key players in the regulation of tissues homeostasis and early inflammatory host responses. ILCs are divided into three groups, and further subdivided into five subsets, that are characterised by distinct transcription factors, surface markers and their cytokine expression profiles. Group 1 ILCs, including natural killer (NK) cells and non-NK cell ILC1s, express T-bet and produce IFN-γ. Group 2 ILCs depend on GATA3 and produce IL-4, IL-5 and IL-13. Group 3 ILCs, composed of ILC3s and Lymphoid Tissue Inducer (LTi) cells, express RORγt and produce IL-17 and IL-22. Even though, the phenotype of each subset is well defined, environmental signals can trigger the interconversion of phenotypes and the plasticity of ILCs, in both mice and humans. Several extrinsic and intrinsic drivers of ILC plasticity have been described. However, the changes in cellular metabolism that underlie ILC plasticity remain largely unexplored. Given that metabolic changes critically affect fate and effector function of several immune cell types, we, here, review recent findings on ILC metabolism and discuss the implications for ILC plasticity.